2022
DOI: 10.1177/00224871221075275
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Beliefs and Their Students’ Progress in Professional Development

Abstract: We respond to calls for more research to address whether and how successful professional development (PD) experiences (defined here in terms of student progress) are related to changes in teacher beliefs, specifically about effective literacy instruction for young struggling readers. We developed a measure, a Teacher Belief Score, to identify teacher beliefs present in interview data and we used student achievement data to create two contrasting groups of teachers, those whose students had lower progress and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
1
0
0
Order By: Relevance
“…These teachers' practices indicated that teachers did not enact their constructivist or transitional epistemological beliefs since they tended to address students' expectations for quick and simple learning for the test preparation. These results aligned with the findings of Mansour (2013) and Rodgers et al (2022) that teachers might modify their beliefs and practices to address students' expectations or students' learning progress. Some teachers held transitional beliefs and suggested the diversity among students, but they rarely addressed the equity issues to address needs of diverse students.…”
Section: Discussionsupporting
confidence: 86%
“…These teachers' practices indicated that teachers did not enact their constructivist or transitional epistemological beliefs since they tended to address students' expectations for quick and simple learning for the test preparation. These results aligned with the findings of Mansour (2013) and Rodgers et al (2022) that teachers might modify their beliefs and practices to address students' expectations or students' learning progress. Some teachers held transitional beliefs and suggested the diversity among students, but they rarely addressed the equity issues to address needs of diverse students.…”
Section: Discussionsupporting
confidence: 86%
“…La formación permanente del profesorado se ha visto ampliada y diversificada en los últimos años. Ella es comprendida como un conjunto amplio que trasciende la noción tradicional del curso (Carrasco y Ortiz, 2023;Hill, et al, 2013;Hilel y Ramírez, 2022;Imbernón, 2020;D'Agostino, et al, 2022), plantean que dicho desarrollo se asocia tambien con la disposición hacia la transformación educativa, y Valillant y Marcelo (2015) señalan que se relaciona con la proyección de la inquietud intelectual del profesorado. Se reconocen otras formas de DPD: acompañamiento de pares expertos, las asistencias técnicas, y, principalmente, las instancias institucionales y sistemáticas de trabajo y aprendizaje colaborativo llevando a cabo procesos de investigación-acción en los establecimientos (Forde, et al, 2021;Harris y Jones, 2011;Vaillant y Marcelo, 2015;Woods y Roberts, 2018).…”
Section: Discusión Y Conclusionesunclassified